2017
DOI: 10.31235/osf.io/takv5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

His and Hers: Economic Factors and Relationship Quality in Germany

Abstract: Research has linked economic factors to relationship quality in the United States, primarily using cross-sectional data. In the current study, 2 waves of the Panel Analysis of Intimate Relationships and Family Dynamics data (n = 2,937) were used to test the gendered association between economic factors and relationship satisfaction among young German couples. In contrast to U.S.-based studies, the findings showed striking gender differences in the association between economic factors and relationship satisfact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…For example, in a nationally representative sample of more than 2,000 individuals in dating, cohabiting, and married relationships in Florida, Maisel and Karney () reported nonsignificant associations between household income and marital quality. A similar study conducted in Germany with nearly 3,000 participants found nonsignificant associations (Hardie, Geist, & Lucas, ). These patterns are also replicated in smaller studies of African American marriages (Bowman & Forman, ; Clark‐Nicolas & Gray‐Little, ).…”
Section: Review and Critique Of Existing Literaturementioning
confidence: 85%
“…For example, in a nationally representative sample of more than 2,000 individuals in dating, cohabiting, and married relationships in Florida, Maisel and Karney () reported nonsignificant associations between household income and marital quality. A similar study conducted in Germany with nearly 3,000 participants found nonsignificant associations (Hardie, Geist, & Lucas, ). These patterns are also replicated in smaller studies of African American marriages (Bowman & Forman, ; Clark‐Nicolas & Gray‐Little, ).…”
Section: Review and Critique Of Existing Literaturementioning
confidence: 85%
“…Relationship satisfaction was measured with the question “How satisfied are you with your current relationship?” The answer categories ranged from 0 ( entirely dissatisfied ) to 10 ( entirely satisfied ). Questions about satisfaction are more stable and have a specific object (here the partner relationship) and are seen less transient and diffuse than moods (for instance, happiness with the relationship; Ilies, Wilson, & Wagner, ) and are widely used to investigate the quality of partner relationships (Blom et al, ; Hardie, Geist, & Lucas, ). The correlation between the partners' relationship satisfaction is 0.491.…”
Section: Methodsmentioning
confidence: 99%
“…Note that we may fail to observe some extremely dissatisfied individuals if relationship dissatisfaction is related to a depressed mood and reduces the willingness to participate in the surveys. We considered this variable to be linear as have many studies (Blom et al, ; Hardie et al, ). Alternatively, other transformations and analyses may be considered such as dichotomizing and ordered logistic regressions, but these have many drawbacks (e.g., having a random cut‐off point; Inanc, ).…”
Section: Methodsmentioning
confidence: 99%
“…The scale ranged from 0 ( completely dissatisfied ) to 10 ( completely satisfied ). Although single‐item measurements are less reliable than multiple‐item scales, this and similar questions are widely used as indicators of relationship satisfaction (e.g., Hardie, Geist, & Lucas, ). See Table for descriptive statistics of all variables.…”
Section: Methodsmentioning
confidence: 99%
“…We used fixed effects models in Stata to test our hypotheses. Fixed effects models have the advantage of modeling changes instead of levels, which could take into account over‐ or underreporting of relationship satisfaction (Hardie et al, ). Essentially the models are difference models wherein the scores are the differences between an individuals' level of relationship satisfaction when they were in one breadwinner arrangement compared with when they were in another breadwinner arrangement averaged over all respondents who were observed in each arrangement.…”
Section: Methodsmentioning
confidence: 99%